2016
DOI: 10.1007/s00787-016-0870-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk factors underlie the link between attention deficit hyperactivity symptoms and overweight at school entry

Abstract: The link between symptoms of attention deficit hyperactivity disorder (ADHD) and increased body weight is well established, while the underlying mechanisms are not yet clear. Since increased body weight and ADHD symptoms have been found to be associated with psychosocial risk factors in childhood, we analyzed whether the psychosocial risks explain the association between the two conditions. The sample consisted of 360 children (age range 6-7 years, 173 boys) attending the obligatory medical health exam before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…The results are in line with another study suggesting the association between ADHD and overweight was completely explained by cumulative psychosocial risks [19]. Prime candidate environmental factors that increase the risk for both ADHD and overweight and that are shared by family members include inadequate health behaviors, foremost poor nutritional habits and lack of physical activity [4851] as well as chronic stress [19]. Poor nutritional habits, lack of physical activity, and chronic stress tend to cluster with each other and within families [19], particularly in families with disadvantaged backgrounds [52].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results are in line with another study suggesting the association between ADHD and overweight was completely explained by cumulative psychosocial risks [19]. Prime candidate environmental factors that increase the risk for both ADHD and overweight and that are shared by family members include inadequate health behaviors, foremost poor nutritional habits and lack of physical activity [4851] as well as chronic stress [19]. Poor nutritional habits, lack of physical activity, and chronic stress tend to cluster with each other and within families [19], particularly in families with disadvantaged backgrounds [52].…”
Section: Discussionsupporting
confidence: 92%
“…This is not in line with a recent review on ADHD and overweight [24], hypothesizing that the association between ADHD and overweight may be primarily linked to deficits in hot executive functions, characterized by impulsivity and difficulties in postponing gratification. The results are in line with another study suggesting the association between ADHD and overweight was completely explained by cumulative psychosocial risks [19]. Prime candidate environmental factors that increase the risk for both ADHD and overweight and that are shared by family members include inadequate health behaviors, foremost poor nutritional habits and lack of physical activity [4851] as well as chronic stress [19].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It can be assumed that unspecified intermediaries have a role in the observed incidence of obesity in children with ADHD. The ADHD-obesity relationship can be explained by genes [ 9 , 12 ], neurobiological features [ 37 ], deficits in executive functions [ 39 ], fetal programming [ 36 ], sleep disorders (circadian rhythm) and incorrect eating habits [ 23 ], high-fat diet [ 22 ], reduced physical activity [ 20 , 21 ], and stress [ 40 ], as well as a sedentary lifestyle. It is also suggested that the association of ADHD with obesity may be a side effect of adaptation to a poor food environment [ 41 ], but few studies have tested this hypothesis and the results are inconclusive [ 1 ].…”
Section: Discussionmentioning
confidence: 99%